The Effect of Work Engagement and Job Satisfaction on Work Motivation and Its Impact on Career Development of Lecturers of Muhammadiyah Aceh University - Yusrizal Yusrizal; Nuzulman Nuzulman; Marlizar Marlizar (Lembaga Teewan Journal Solutions, 2026)
The purpose of this research is to examine the conditions of work engagement, job satisfaction, work motivation, and career development; the effect of work engagement on lecturers’ career development; the effect of job satisfaction on career development; the effect of work engagement on lecturers’ work motivation; the effect of job satisfaction on lecturers’ work motivation; the effect of work motivation on career development; the effect of work engagement on performance through lecturers’ work motivation; and the effect of job satisfaction on performance through lecturers’ work motivation. The objects of this study are work engagement and job satisfaction in relation to work motivation and their implications for lecturers’ career development. This research was conducted at Universitas Muhammadiyah Aceh with a total of 132 lecturer respondents. The data analysis tools used in this study were descriptive tests to examine the descriptive statistical model based on mean values, and verification tests using structural equation modeling (SEM) with the help of the AMOS program. The results of the study show that work engagement, job satisfaction, work motivation, and career development have been well implemented. Work engagement and job satisfaction have a significant influence on lecturers’ work motivation; work motivation has a significant effect on lecturers’ career development; work engagement and job satisfaction significantly affect career development; and work engagement and job satisfaction also influence career development through lecturers’ work motivation at Universitas Muhammadiyah Aceh.